Cue-based feeding in the NICU—a pathway to earlier oral feeding of preterm infants - Ofek Shlomai, Noa; Mordechai, Chen; Morag, Iris; Bdolach Abram, Tali; Eventov Friedman, Smadar (Frontiers in Pediatrics, 2024)
Aim: To compare volume driven and cue-based feeding of preterm low-birth-weight infants, regarding short term outcomes, including transition to oral feeds, weight gain, and length of stay. Methods: This was a retrospective cohort study. Feeding and weight gain outcomes were compared between infants fed by volume driven and cue-based feeds. the groups were subdivided by birth weight categories. Results: Study group included 240 low birth weight preterm infants born before 34 weeks of gestation, 120 infants fed by volume driven feeding were compared to 120 infants fed by cue-based feeding. The groups were sub analyzed by birth weight categories, <1,500 gr, and 1500-2,500 gr. Study groups were comparable regarding baseline characteristics and neonatal morbidities. Infants fed by cue-based feeding were more likely to achieve full oral feeding faster, and at an earlier gestational age. Infants with birth weight of <1,500 gr were less likely to experience adverse respiratory episodes during cue-based feeding. Although weight gain rate was reduced in the cue-based feeding in the heavier infant group, discharge weight, breast-feeding rates, and length of stay, were comparable between the groups. Conclusions: Cue-based feeding results in faster transition to full oral feeding in preterm very-low-birth infants, and at an earlier gestational age. Key notes: • Transition to oral feeding is a challenge for low-birth-weight preterm infants. • Cue-based feeding is a feeding method which is responsive to the infants’ cues of satiety and hunger. • Cue-based feeding results in faster transition of low-birth-weight infants to full oral feeding, at an earlier gestational age, with increased cardiorespiratory stability.